An Electrophilic Bromine Redox Catalysis for the Synthesis of Indole Alkaloid Building Blocks by Selective Aliphatic C−H Amination. Issue 48 (7th November 2018) - Bergès, Julien; García, Belén; Muñiz, Kilian
Abstract: A new homogeneous bromine(−I/I) redox catalysis is described, which is based on monomeric bromine(I) compounds containing transferable phthalimidato groups. These catalysts enable intermolecular C−H amination reactions at previously unaccessible aliphatic positions and thus enlarge the synthetic potential of direct C−N bond formation, including its application in the synthesis of alkaloid building blocks. This aspect is demonstrated by a new synthetic approach to aspidospermidine. In addition to the development of the catalyst system, the structures of the involved bromine(I) key catalysts were fully elucidated, including by X‐ray analyses. Abstract : New cat. on the block : C−H amination can be conveniently accomplished within a unique Br(−I/I) catalyst system, which opens versatile access to the synthesis of alkaloid building blocks.